Comprehensive Analysis of circRNAs, miRNAs, and mRNAs Expression Profiles and ceRNA Networks in Decidua of Unexplained Recurrent Spontaneous Abortion - Liu, Xiaohua; Wu, Jiabao; Nie, Hua; Zhu, Xiaoli; Song, Ge; Han, Lu; Qin, Weibing (Frontiers in Genetics, 2022)
The diagnosis and treatment of unexplained recurrent spontaneous abortion (URSA) are subject to debate, because the exact underlying mechanisms remain unclear. To address this issue, we elucidated the expression profiles of dysregulated circRNAs, miRNAs, and mRNAs and constructed circRNA-associated competitive endogenous RNA (ceRNA) networks by comparing the decidua of URSA with that of normal early pregnancy (NEP) using RNA-sequencing. In total, 550 mRNAs, 88 miRNAs, and 139 circRNAs were differentially expressed (DE) in decidua of URSA. Functional annotation revealed that DE mRNAs as well as potential target genes of DE miRNAs and DE circRNAs are mainly involved in immunologic function, such as antigen processing and presentation, allograft rejection, and T cell receptor signaling pathway. In addition, the top hub genes, including CCL4, DDX58, CXCL10, CXCL9, MX1, CD44, RPS2, SOCS3, RPS3A, and CXCL11, were identified. The mRNAs involved in ceRNA network were enriched in complement and coagulation cascades and protein processing in the endoplasmic reticulum. We found that circRNAs in the ceRNA network, which acted as decoys for hsa-miR-204-5p, were positively correlated with MFGE8. Collectively, the results demonstrated that circRNAs, miRNAs, and mRNAs were aberrantly expressed in the decidua of patients with URSA and played a potential role in the development of URSA. Thus, the establishment of the ceRNA network may profoundly affect the diagnosis and therapy of URSA in the future.